Optimizing Concrete Construction: Enhancing Strength and Durability through Proper Vibrator Utilization - Latief, Awang Muhammad; Noor, Rusandi; Laksamana, Bagus (JSE Journal of Science and Engineering, 2024)
Concrete, known for its high compressive strength and resistance to environmental degradation, proves ideal for durable building construction if implemented correctly. Mix designers, implementers, and supervisors must comprehend concrete properties to prevent errors in construction. Vibrators play a crucial role in enhancing concrete quality and strength during casting, facilitating air removal, ensuring even distribution, and increasing density. This research evaluates the impact of vibrators on mechanical properties and strength, utilizing a hammer test to compare unconfined compressive strength in samples cast with and without vibrators. Results indicate that vibrators significantly enhance concrete compactness, reduce cracking risk, and improve pressure resistance. Additionally, they positively influence aggregate distribution and reduce porosity. Integrating vibrators into the casting process is essential, offering tangible benefits for structural performance and building durability. Practical implications include guidance on optimal vibrator use in construction projects for superior outcomes. Concrete damage poses a common challenge in construction, affecting elements like columns, beams, plates, and walls. Conducting case studies on damage causes is crucial to identify and minimize potential issues, ensuring the long-term integrity of structures.